Tangerine quality monitoring by ethanol concentration measurement - Wongsila S. (2014)
The objective of this work is attributed to postharvest quality of 'Sai Nam Pung' tangerine. The ethanol concentration of the tangerine quality was monitored during keeping. Commercially, a tangerine is coated with wax in order to increase the shelf-life. However, the waxed tangerine can generate an anaerobic respiration known as "fermentation" which has an effect on the tangerine quality. As a result of the fermentation, ethanol is produced. In this work we have tested the tangerine quality with our home-made alcohol meter based on a semiconductor oxide gas sensor. The alcohol meter is designed to measure four tangerines at the same time. The ethanol, diffused from the tangerine surface, was measured by the alcohol meter in a close system at a constant temperature of 35oC. In order to check the capability of the home made system, the alcohol meter was calibrated with standard ethanol solutions. With these standard solutions, the tangerine quality was classified to 3 levels which are 25 ppm, 50 ppm and 75 ppm. The ethanol level results were compared with the human taste. For human score, the tangerine was orally tasted by trained specialist then a score was given. From the experimental results, a correlation between the human scores and the ethanol levels was determined and can be used for indicating the tangerine quality. From the correlation results, the home-made alcohol meter can be used for continuously monitoring the tangerine quality in a non-destructive way.